Enhanced DPPH Radical Scavenging Activity and Enriched γ-Aminobutyric Acid in Mulberry Juice Fermented by the Probiotic Lactobacillus brevis S3 - Luchan Gong; Tingting Li; Jian Feng; Jiamin Yin; Xiaozhou Zou; Jun Wang; Bowen Wang (Fermentation, 2023)
Mulberries, known for their high sugar content and rich bioactive compounds, have attracted attention for their potential health benefits. γ-Aminobutyric acid (GABA) is an amino acid with multiple physiological functions. To increase the GABA content and enhance the antioxidant capacity in fermented mulberry beverages, we screened a high-yielding strain, Lactobacillus brevis S3, known for its probiotic properties. L. brevis S3 demonstrated an excellent tolerance to simulated gastric acid, gastric juice, intestinal fluid, bile salts, osmotic pressure, and phenol, making it a safe and valuable probiotic candidate for mulberry fermentation. We attempted the addition of different nutritional components to enhance the GABA content in mulberry juice, including 1% yeast extract; 0.5% peptone; 0.01% metal ion complex (magnesium sulfate, manganese sulfate, and ferrous sulfate); combinations of yeast extract and peptone, and all three components. Mulberry juice supplemented with all three components reached a viable cell count of 1.2 × 1010 CFU/mL after 72 h. The antioxidant capacity and GABA titer were enhanced. The DPPH free radical scavenging capacity increased by 1.62 times, and the GABA content reached 7.48 g/L. By utilizing L. brevis S3 with excellent probiotic properties and supplementation with nutritional components, it is possible to produce low-sugar mulberry functional beverages with a high DPPH free radical scavenging capacity that are rich in GABA.